PENGARUH KEWAJIBAN MORAL, KUALITAS PELAYANAN, DAN SANKSI PERPAJAKAN PADA KEPATUHAN WAJIB PAJAK DI KPP BADUNG UTARA - Artha, Ketut Gede Widhi; Setiawan, Putu Ery (E-Jurnal Akuntansi; Vol 17 No 2 (2016), 2016)
This study aims to determine the effect of moral obligation, the quality of services, and tax penalties against an individual taxpayer compliance in the scheme of PP 46 In 2013 in North Badung STO. This study uses a questionnaire as a method of data collection. By using Slovin formula obtained a hundred  respondents in the sample in this study. Based on the results of the discussion, a moral obligation, quality of service, and tax penalties positive effect on compliance of individual taxpayers in the scheme of PP 46 in 2013. The higher the moral obligation, the better quality of service and increasingly strict tax penalties will have no effect on the higher level of compliance of individual taxpayers.
Keywords: moral obligation, quality of service, tax penalties, and compliance of individual taxpayers in the scheme of PP 46 in 2013